PENGUATAN PERAN PARTAI POLITIK DALAM PEMILIHAN UMUM LEGISLATIF PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 114/PUU-XX/2022 - Kartabrata, Fajar Ramadhan (Faculty of Law, Universitas Pasundan, 2023)
The Constitutional Court Decision Number 114/PUU-XX/2022 emphasizes the necessity of implementing the electoral system through proportional representation with an open list. This decision aims to strengthen the role of political parties as participants in the electoral process, ensuring high-quality and dignified elections in line with constitutional principles. Such affirmation is rooted in a critical paradigm shift for political parties as key pillars of democracy. This research employs a juridical-normative analysis approach, delving into secondary data through literature reviews. The research findings indicate the central role of the Constitutional Court as the final interpreter of the constitution and the guardian of democratic integrity. Decision Number 114/PUU-XX/2022 provides a profound interpretation of the constitution, aimed at improving the implementation of political parties' participation in elections. Although the Constitutional Court's considerations are non-executorial, its guidelines offer crucial insights into conducting democracy in line with the constitutional spirit through elections. Keywords: Political Parties, Elections, Constitutional Court, Democracy.